Law professor put on trial for ‘trespassing’ on family’s ancestral lands - Rogin, Jillian; Bahdi, Reem; McAdam, Sylvia (The Conversation, 2019)
A co-founder of Idle No More was put on trial for ‘trespassing’ on her family’s ancestral lands. Canada has much to learn about institutionalizing respectful relationships with Indigenous peoples.
Keywords: Jillian Rogin; Reem Bahdi; Sylvia Mcadam